Analisis Strategi Pemasaran Online dan Offline Toko Kue Ulang Tahun Mhira Cake Tepian Indah Bengalon dalam Prinsip Etika Pemasaran Islam - Selviana Selviana; Mustatho Mustatho; Ulfa Jamilatul Farida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Marketing strategy is a fundamental aspect that must be considered in order to achieve predetermined marketing objectives. This strategy encompasses a series of steps and decisions taken to promote products, reach the right target market, and influence customer purchasing behavior. The purpose of this study is to identify the strategies employed by the Mhira Cake Birthday Cake Shop in every sales or promotional activity to attract customer interest, as well as to analyze these strategies from the perspective of Islamic marketing principles. This research is classified as field research, in which the writer directly visited the location—Mhira Cake Birthday Cake Shop—to obtain accurate data, employing a qualitative research approach. The primary informant in this study was the owner of Mhira Cake, while supporting informants included the shop’s customers. Data collection techniques included observation, interviews, and documentation. The collected data were then processed and analyzed using a descriptive qualitative method. The results of this study show that Mhira Cake employs marketing strategies through product, pricing, promotion, and location. The marketing methods used include offering affordable prices for the products sold. From the perspective of Islamic economics, it can be concluded that the marketing strategies implemented by Mhira Cake are in accordance with Islamic marketing principles. The shop operates its business based on values of honesty and fairness and applies characteristics aligned with Islamic marketing ethics. Additionally, in practice, the business incorporates ethical business conduct by demonstrating the traits of shiddiq (truthfulness), amanah (trustworthiness), tabligh (transparency in communication), and fathonah (wisdom). The business is run with a commitment to integrity in every aspect.